Sensory Neuron Expressed FcγRI Mediates Postinflammatory Arthritis Pain in Female Mice - Liu, Yan; Caterina, Michael J.; Qu, Lintao (Frontiers in Immunology, 2022)
Persistent arthritis pain after resolution of joint inflammation represents a huge health burden in patients with rheumatoid arthritis (RA). However, the underling mechanisms are poorly understood. We and other groups recently revealed that FcγRI, a key immune receptor, is functionally expressed in joint nociceptors. Thus, we investigated a potential role of sensory neuron expressed FcγRI in postinflammatory arthritis pain in a mouse model of collagen antibody-induced arthritis (CAIA). Here, we show that global deletion of Fcgr1 significantly attenuated mechanical hyperalgesia in the ankle and hind paw of female mice in both inflammatory and postinflammatory phases of CAIA. No obvious differences in cartilage destruction were observed after resolution of joint inflammation between genotypes. In situ hybridization (ISH) revealed that a larger proportion of dorsal root ganglion (DRG) neurons expressed Fcgr1 mRNA signal in the late phase of CAIA. Conditional deletion of Fcgr1 in primary sensory neurons produced similar analgesic effects without affecting joint swelling. Knockdown of Fcgr1 expression within DRG in the postinflammatory phase of CAIA alleviated persistent pain. Inflammation within DRG after resolution of joint inflammation in the CAIA model was evidenced by T cell and neutrophil infiltration and upregulated mRNA expression of numerous inflammatory mediators. Yet, such changes were not altered by genetic deletion of Fcgr1. We suggest that neuroinflammation within the DRG after resolution of joint inflammation might upregulate FcγRI signaling in DRG neurons. Sensory neuron expressed FcγRI thus merits exploration as a potential target for the treatment of arthritis pain that persists in RA patients in remission.